Pharmacokinetics of fluorouracil by intravenous or intraarterial injections - Geng Bao-Qin; Zhu Yong-Lian (Acta Pharmacologica Sinica, 2016)
The high-performance liquid chromatographic analysis of fluorouracil (5-FU) content in blood and colon of rabbits was described. There was no marked difference in the plasma 5-FU level and blood concentration-time curve following iv (ear vein) or ia (inferior mesenteric artery) injections of 5-FU 15 mg/kg. However. the distribution of 5-FU in colon given by ia was quite different from those of iv. At 10, 20 and 30 min after ia, the 5-FU content in colon was shown to be 31-, 17- and 14-fold higher than those of iv. respectively. Colonic tissue AUC0-480 min were 2453 and 690 min.mg/ml (p